PENGELOLAAN UNSUR HARA TERPADU DALAM BUDIDAYA TANAMAN PORANG (REVIEW) - Ria Rustiana; Suwardji Suwardji; Ahmad Suriadi (Jurnal Agrotek Ummat, 2021)
Elephant food yam (Amorphophallus muelleri Blume) is an important tuber plant that is grown in most of the tropical countries including Indonesia and is a very profitable export commodity. Soil nutrients availability is one of the most important factors that determine the production of elephant food yam plants. However, there is no single nutrient source, either from inorganic fertilizers or organic fertilizers or biological fertilizers, which is able to meet all the nutrient needs of the plants grown. Therefore, integrated nutrient management (INM) of elephant food yam plants seems to be a way out to maintain sustainable production and increase profitability. This paper reviews the results of research on various issues of INM-based production management for elephant food yam plants and analyzes the extent of research on the use of INM both in Indonesia and abroad. The benefits of integrated nutrient management are well documented for vegetable crops. However, it is still very little available for elephant food yam plants, especially in Indonesia. Integrated nutrient management (INM) is a very important technological innovation to be applied to elephant food yam cultivation. Elephant food yam is a high nutrient consumeplant, so a wise and precise combination of inorganic and organic fertilizers as well as bio-fertilizer will result in sustainable and sinergistic use of soil nutrients of elephant foot yams. Therefore, recommendations for research need for INM of elephant food yam should be carried out in order to increase the production of it in a sustainable manner.